2020
DOI: 10.1155/2020/3484659
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Plasma Exchange as a Treatment for Autoimmune Neurological Disease

Abstract: Introduction. Therapeutic plasma exchange (TPE) is commonly used as treatment of certain autoimmune neurological diseases (ANDs), and its main objective is the removal of pathogenic autoantibodies. Our aim was to describe the clinical profile and the experience with the usage of TPE in patients with ANDs at our institution. Methods. This is an observational retrospective study, including medical records of patients with diagnosis of ANDs who received TPE, between 2011 and 2018. Characteristics of TPE, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…This technique is widespread to reduce the concentration of cytokines and inflammatory mediators. It could be used even in non-infectious inflammation [ 30 ]. FFP used in the PE could decrease the inflammatory cytokines and modulate the hypercoagulation by providing the ADAMTS13 enzyme [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This technique is widespread to reduce the concentration of cytokines and inflammatory mediators. It could be used even in non-infectious inflammation [ 30 ]. FFP used in the PE could decrease the inflammatory cytokines and modulate the hypercoagulation by providing the ADAMTS13 enzyme [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plasmapheresis is one of these. It is an extracorporeal circulation therapy to remove pathogenic molecules from the blood of patients with autoimmune disorders [5][6][7][8].…”
mentioning
confidence: 99%
“…The basic safety analysis of the AMBAR trial previously reported that 90% of the PE procedures were uneventful, 31 as expected based on the safety profile for PE previously reported. 37,[41][42][43] The high percentage of finalized procedures and the relatively low incidence of AEs highlighted the feasibility and safety, respectively, of this procedure in mild-to-moderate AD patients. Here we extended the safety analysis emphasizing the procedure type (TPE vs LVPE), the different PE treatment modalities (albumin doses; with/without IVIG) and TPE venous access (central vs peripheral).…”
Section: Discussionmentioning
confidence: 99%